Optimal age of breeding gilts and its impact on lifetime performance - Malanda, Joab; Balogh, Péter; Novotni Dankó, Gabriella (Acta Agraria Debreceniensis, 2019)
Age at first breeding and lifetime reproductive performance was analyzed on 17,558 F1 Landrace x Yorkshire gilts from 9 piglet producing herds of Midwest, United States entered in herds between 1st Jan 2014 and 31st July 2016. At the time of data collection Dec 2018, 15% of the sows were still active in the herds hence excluded from the analysis. Individual gilt data included date of birth, age in days at first mating, piglet total born by parity, lifetime piglet total born and reason for culling. Quality data checks were done before analysis to eliminate all outlier values together with sows that had no entry information for any listed category. The total database of the sows was classified into 6 classes according to age at the first mating in days 170-190(n=754), 191-211(n=4683), 212-232(n=7123), 233-253(n=3385), 254-274(n=1002) and 275-369 (n=611). Piglet total born obtained from each sow during the lifetime production was significantly (P < 0.05) greater for gilts bred between 233-253 days of age at first mating. Gilts that were bred at